1988
DOI: 10.1083/jcb.106.4.1221
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of actin by positively charged liposomes.

Abstract: Abstract. By cosedimentation, spectrofluorimetry, and electron microscopy, we have established that actin is induced to polymerize at low salt concentrations by positively charged liposomes. This polymerization occurs only at the surface of the liposomes, and thus monomers not in direct contact with the liposome remain monomeric. The integrity of the liposome membrane is necessary to maintain actin in its polymerized state since disruption of the liposome depolymerizes actin. Actin polymerized at the surface o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
48
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 49 publications
7
48
1
Order By: Relevance
“…But it is clear from the experiments done in Gbuffer that actin has to be in the form of polymerised filaments to adsorb to positively charged monolayers. This is in contradiction with the results of Laliberte and Gicquaud [30] who observed a polymerisation on positively charged vesicles (phosphatidylcholine and stearylamine 90/10), although the experiments were done in depolymerising buffer. However, our results are consistent with those of Taylor and Taylor who observed that quaternary ammonium surfactants are better promoter of 2-D crystal growth than stearylamine.…”
Section: Discussioncontrasting
confidence: 84%
“…But it is clear from the experiments done in Gbuffer that actin has to be in the form of polymerised filaments to adsorb to positively charged monolayers. This is in contradiction with the results of Laliberte and Gicquaud [30] who observed a polymerisation on positively charged vesicles (phosphatidylcholine and stearylamine 90/10), although the experiments were done in depolymerising buffer. However, our results are consistent with those of Taylor and Taylor who observed that quaternary ammonium surfactants are better promoter of 2-D crystal growth than stearylamine.…”
Section: Discussioncontrasting
confidence: 84%
“…A previous study (12) demonstrated that actin binding to the lipid-bilayer membrane could be suppressed when the membrane was made from a mixture ofneutral and negatively charged lipids.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, we found that actin solutions at higher concentrations became birefringent upon actin polymerization, indicating that spontaneous alignment of actin filaments occurred without liposomes (unpublished work). However, this alignment occurred on a much larger scale than that with liposomes; the size of the birefringent area was -10-20 Aum wide and 100 Am long, whereas the size ofthe liposomes was only up to [10][11][12][13][14][15][16][17][18][19][20] Aum in width and length in most cases. In addition, we observed no tendency of the aligned filaments in solution to form circular structures.…”
Section: Discussionmentioning
confidence: 99%
“…This mixture also avoided aggregation of vesicles (apparent with PtdCho or PtdEtn/phosphatidylserine vesicles) (17). The negatively charged surface prevented actin polymerization directly from the membrane (18 There were no detectable differences in the shapes of vesicles prepared by dilution or by using Centrex concentrators. FPR.…”
mentioning
confidence: 93%